Wound assessment tools and nurses’ needs: an evaluation study - Greatrex-White, Sheila; Moxey, Helen (Wiley, 2013)
The purpose of this study was to ascertain how well different wound assessment tools meet the needs of nurses in carrying out general wound assessment and whether current tools are fit for purpose. The methodology employed was evaluation research. In order to conduct the evaluation, a literature review was undertaken to identify the criteria of an optimal wound assessment tool which would meet nurses’ needs. Several freely available wound assessment tools were selected based on predetermined inclusion and exclusion criteria and an audit tool was developed to evaluate the selected tools based on how well they met the criteria of the optimal wound assessment tool. The results provide a measure of how well the selected wound assessment tools meet the criteria of the optimal wound assessment tool. No tool was identified which fulfilled all the criteria, but two (the Applied Wound Management tool and the National Wound Assessment Form) met the most criteria of the optimal tool and were therefore considered to best meet nurses’ needs in wound assessment. The study provides a mechanism for the appraisal of wound assessment tools using a set of optimal criteria which could aid practitioners in their search for the best wound assessment tool.